LGBT and Same-Sex Marriage: Marriage Nature in State Religious, Quran and Hadith Norms - Faqih, Yurika Anidza; Khamim (Media of Law and Sharia, 2025)
The phenomenon of LGBT and same-sex marriage has been a long-standing problem and debate to this day, where it is contrary to the essence of marriage and human nature. Islamic law and positive law in Indonesia also oppose this because it is not in accordance with the religious values and morality of Indonesian society. The focus of this research is to describe the existence of LGBT and marriage in Indonesia within state norms and analyze based on the Koran and hadith the nature of marriage towards LGBT and same-sex marriage. This research uses normative legal research or can be called library research with a conceptual approach. The results of this research are that the existence of LGBT and same-sex marriages grows and develops in line with existing empirical facts, caused by several factors and damaging the moral ethics of religion and nation and in this case the sanctions for this behavior have not been determined with certainty due to legal ambiguity.In state regulations, namely in Article 292 of the Criminal Code. Meanwhile, in the analysis of the Al-Qur'an and Hadith in Qs. An-Nisa' (1) and Sahih Muslim that LGBT and same-sex marriage violate the essence of marriage, namely not marriage between a man and a woman, sexual orientation is only to fulfill thebiological aspect and not the entire psychological and spiritual aspect and violates the objectives of Islamic law, namely Maqashid Sharia specifically Hifdz an-Nasl, because they cannot continue their descendants afterwards.